Key Structures and Interactions for Binding of Mycobacterium tuberculosis Protein Kinase B Inhibitors from Molecular Dynamics Simulation. (24th November 2014) - Punkvang, Auradee; Kamsri, Pharit; Saparpakorn, Patchreenart; Hannongbua, Supa; Wolschann, Peter; Irle, Stephan; Pungpo, Pornpan
<x xml:space="preserve">Abstract</x> Substituted aminopyrimidine inhibitors have recently been introduced as antituberculosis agents. These inhibitors show impressive activity against protein kinase B, a Ser/Thr protein kinase that is essential for cell growth of M. tuberculosis. However, up to now, X‐ray structures of the protein kinase B enzyme complexes with the substituted aminopyrimidine inhibitors are currently unavailable. Consequently, structural details of their binding modes are questionable, prohibiting the structural‐based design of more potent protein kinase B inhibitors in the future. Here, molecular dynamics simulations, in conjunction with molecular mechanics/Poisson–Boltzmann surface area binding free‐energy analysis, were employed to gain insight into the complex structures of the protein kinase B inhibitors and their binding energetics. The complex structures obtained by the molecular dynamics simulations show binding free energies in good agreement with experiment. The detailed analysis of molecular dynamics results shows that Glu93, Val95, and Leu17 are key residues responsible to the binding of the protein kinase B inhibitors. The aminopyrazole group and the pyrimidine core are the crucial moieties of substituted aminopyrimidine inhibitors for interaction with the key residues. Our results provide a structural concept that can be used as a guide for the future design of protein kinase B inhibitors with highly increased antagonistic activity.